Face-to-face versus online-based lectures: A COVID-19 induced study on assessments - Fisher, David; Solomons, Deon; Makhathini, Khayelihle Brian (Frontiers in Education, 2022)
There is much debate regarding the impact of COVID-induced lockdown on the standard of assessments, mainly since students were assessed at home via an online assessment platform, Ikamva. Regular orthodox lectures and assessments were carried out during the first term, while the strictly enforced South African COVID lockdown warranted that 2nd term lectures and assessments were based online. This created the fortunate control conditions to statistically compare orthodox face-to-face with online-home-based assessments. We compared the assessments of a cohort of second-year students studying physiology and anatomy during 2019 and 2020: Orthodox face-to-face teaching and assessments (2019) were compared to online teaching and their analogous online assessments (2020) during the COVID-19-induced lockdown. Although class pass rates and marks for online assessments (2020) were significantly higher than for orthodox assessments (2019), an essential finding of the study was that the Gaussian distribution of the marks across the class for both modes of assessment was statistically identical. This indicated that although students performed better with home-based online assessments, poor-performing students populated the lower spread of marks, modal students occupied the central distribution while good students occupied the higher mark distribution of the curve. The students were found to be resilient in adapting to hing and learning, online presentations, and computer-based assessments. No gender-based difference or advantage to adjusting to newly introduced blended learning and concomitant changes in learning assessment strategies was found. The online-home-based assessments (iKamva), proved to incentivize prior learning and preparation for assessments, by implementing strict time limits or assessments and randomizing the selections of questions and respective MCQ answer choices. We conclude that although home-based online assessments significantly improve the overall mark distribution, there was no distinction in the spread of the distribution of marks, which was indicative that the home-based online assessment process was able to provide an identical measure of course proficiency as in the orthodox sit-down assessment. Therefore, our statistical analysis of the performance of students under student assessment performances indicates that there is no rationale for thinking that home-based online mode of assessment is equivalent to or better than the orthodox modes of assessment.